Witnessing postwar traumas and memories on film - Borjan, Etami (2011)
The films analyzed in the paper focus primarily on individual traumas and memories that serve as political commentary on the effects of violence done to the whole social fabric. Individual trauma thus becomes metaphor for collective trauma and the direct documentary style makes the film a tool for personal and collective psychoanalysis. By witnessing their pain in front of the camera, the subjects witness their experience of subjugation to the nationalist “regimes of truth”. Coming to terms with the post-war traumas means coming to terms with the recent traumatic history and defining one’s own identity in the post-war society.